The Role of Affect in Cross-Cultural Negotiations - George, Jennifer M.; Jones, Gareth R.; Gonzalez, Jorge A. (Journal of International Business Studies, 1998)
This paper presents a model of cross-cultural negotiations which describes how the affect negotiators experience during negotiations influences the character of the negotiation process and its outcomes. Three categories of determinants of negotiator affect are proposed: Individual differences, cross-cultural differences, and contextual factors. The ways in which negotiator affect influences information processing during negotiations are then described. It is suggested that the influence of affect, through substantive information processing, may lead to either positive or negative spirals in negotiations, influencing the ability of negotiators to reach an integrative solution. Finally, the ways in which negotiators can break out of destructive negative spirals by engaging in motivated rather than substantive information processing are discussed.